ASSESSMENT OF THE IMPLEMENTATION OF THE RAW MATERIAL INVENTORY ACCOUNTING INFORMATION SYSTEM TO IMPROVE INTERNAL CONTROL EFFECTIVENESS AT PT. DIC GRAPHICS INDONESIA (MOJOKERTO PLANT) - Fendy Mulyo Galih Gumilang; Fityan Izza Noor Abidin (International Journal of Business, Law and Political Science, 2025)
Objective: The purpose of this study is to determine the application of the raw material inventory accounting information system and internal control of the raw material inventory accounting system at PT. DIC Graphics Indonesia (Plant Mojokerto). Method: The research method used is qualitative. The population was taken from PT. DIC Graphics Indonesia (Plant Mojokerto) located on Jalan Mandek, Kutogirang, Ngoro District, Mojokerto Regency, East Java. Sampling using purposive sampling technique. The data source was obtained from the interview process which was conducted directly to the PPIC informant Mr. Ridho, the warehouse head Mr. Iwan and the warehouse admin Mr. Bagus, and other data sources in the form of archive sources obtained from data at PT. DIC Graphics Indonesia (Plant Mojokerto) as complementary secondary data. Data analysis is a planned procedure in collecting, organizing, interpreting, and interpreting data that has been combined in order to interpret the given phenomenon or make decisions based on empirical evidence. This technique has 3 steps, (1) data reduction, (2) presenting data, and (3) Verification (Drawing Conclusions). Result: The results of the study on the implementation of the raw material inventory accounting information system at PT. DIC Graphics Indonesia (Mojokerto Plant) have carried out the procedures as determined by the company and include: identifying each type of raw material used in the production process, recording the entry and exit of raw materials from the inventory warehouse using a computerized system and the implementation of the raw material inventory accounting system at PT. DIC Graphics Indonesia (Mojokerto Plant) has been proven to improve the company's internal control. Novelty: The study highlights the improvement in internal control through the implementation of a computerized raw material inventory accounting information system at PT. DIC Graphics Indonesia (Mojokerto Plant).